Antibacterial properties of cationic copolymers as a function of pendant alkyl chain length and degree of quaternization - ABDURRAHMANOĞLU, SUZAN (WILEY, 2021)
Antibacterial polymers are promising materials in the fight against bacterial infection which is a vital health problem. Among these materials, cationic (co)polymers with quaternary ammonium groups are of great interest and importance as they interact with the bacterial membrane causing cell death. The antibacterial efficacy can be improved by modifying the pendant alkyl groups and charge density of the polycation. In this study, alkylbromides with different chain lengths were used to obtain quaternized poly(4-vinylpyridine-co-N-vinylpyrrolidone) (P(4VP-co-NVP)) copolymers of various positive charge densities and pendent alkyl chain lengths. While the chemical structures of the produced copolymers were characterized by Fourier transform infrared and H-1 NMR spectroscopy, physicochemical properties such as size and zeta potential were measured by dynamic light scattering spectrometry. It was determined that the zeta potentials and hydrodynamic diameters of the samples vary between +10 and +32 mV and 10 and 16 nm, respectively. The antibacterial activity of the copolymers were tested against Escherichia coli and Staphylococcus aureus bacteria by broth microdilution and standard 'plate' count methods. The results revealed that the antibacterial activity of the copolymers against Escherichia coli can be successfully adjusted through varying the chain length of the alkylating agent (hydrophobic chains) and the degree of quaternization (positive charge density). (c) 2020 Society of Chemical Industry
Keywords: antibacterial; polycation; quaternization; 4‐ vinylpyridine; N‐ vinylpyrrolidone; NANOPARTICLES; POLY(4-VINYLPYRIDINE); POLYMERS